390 Adaptation and Evaluation of Guideline-Based Family-Based Behavioral Treatment for Overweight and Obesity in Childhood Survivors of Acute Lymphoblastic Leukemia (ALL). (April 2022) - Jakubiak, Jessica; Wilfley, Denise; King, Allison; Hayashi, Robert J.
Abstract : OBJECTIVES/GOALS: Childhood survivors of ALL are at considerable risk for late effects which are exacerbated by excess weight. The proposed study involves the adaption and evaluation of the first empirically supported intervention for childhood survivors of ALL that is consistent with all national recommendations for the treatment of childhood obesity. METHODS/STUDY POPULATION: The proposed intervention will be adapted from family-based behavioral weight loss treatment (FBT) a multicomponent intervention which targets diet, activity, behavioral skills, parenting, and social facilitation among children and their parents. The Framework for Reporting Adaptations and Modifications-Enhanced structure (FRAME), a dissemination and implementation framework, will guide the adaptation, allowing for the incorporation of feedback previously gathered from key stakeholders. A single-arm, non-randomized trial of the adapted intervention will then be conducted to evaluate its acceptability, feasibility, and preliminary indications of efficacy including measures of relative weight change and associated health-related behaviors among 40 childhood ALL survivors and their families. RESULTS/ANTICIPATED RESULTS: Self-reported feedback from families at the end of treatment (EoT) is anticipated to demonstrate that this intervention will be regarded as both acceptable and feasible. Other measures of feasibility will include attendance and retention rates, which are expected to reflect to those of previous FBT trials (92% and 85%, respectively). Preliminary indications of the efficacy of the adapted intervention will be investigated through the comparison of a series of measurements taken at both baseline and EoT. Changes in relative weight will be assessed and are expected to meet a previously established range of clinically meaningful reduction in child percent overweight of 9 units or more. Improvements in dietary intake, physical activity, and health related quality of life are also anticipated. DISCUSSION/SIGNIFICANCE: Knowledge gained from the implementation of the first evidence-based intervention adapted for childhood survivors of ALL will be critical to the justification of a larger-scale, randomized controlled trial and holds promise to effectively modify the risk for chronic disease among a vulnerable population.